2012
DOI: 10.1331/japha.2012.11132
|View full text |Cite
|
Sign up to set email alerts
|

PictureRx: Illustrated medication instructions for patients with limited health literacy

Abstract: Objectives To describe (1) the role of illustrated medication instructions in pharmacy practice, (2) the evidence for their use, and (3) our experience with their implementation. Practice description PictureRx is applicable to all pharmacy practice settings. Practice innovation PictureRx enables pharmacists to rapidly produce evidence-based, illustrated medication instructions that are well-understood by patients of all health literacy levels. Results PictureRx has been studied in a number of settings. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Consistent with studies of adult patients, Yin et al . showed that pictographic interventions might only be helpful to the caregivers with limited health literacy .…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Consistent with studies of adult patients, Yin et al . showed that pictographic interventions might only be helpful to the caregivers with limited health literacy .…”
Section: Discussionsupporting
confidence: 77%
“…30,32,38 In fact, comprehension of the complicated pharmaceutical instructions can be improved by simplifying the text and strengthening the correspondence between pictures and text. 42 Consistent with studies of adult patients, 30,32,[37][38][39] Yin et al showed that pictographic interventions might only be helpful to the caregivers with limited health literacy. 44 However, the findings of Tork suggested that the usefulness of pictorial aids might not 46 High High Unclear Unclear Low Unclear Low significantly vary across health literacy levels.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…To solve this problem, it would be interesting to add illustrations to help patients with low levels of literacy to improve their understanding of how medicines should be used. Indeed, a study showed that this type of illustration could reduce errors both in the dosage of the medicine and resolve doubts about the part of the body where medication should be applied, at the same time increasing the degree of satisfaction with the care received in the community pharmacy in patients with low ML showed (36,37). However, another study carried out with that the use of illustrations did not reinforce the information received only in written form (38).…”
Section: Discussionmentioning
confidence: 99%